Abnormal CD40 Ligand (CD154) Expression in Human Immunodeficiency Virus-Infected Children - O'Gorman, Maurice R. G. (American Society for Microbiology, 2001)
The CD40 ligand (CD154), expressed primarily on activated CD4-positive T cells, is a costimulatory molecule involved in B-cell proliferation, germinal center formation, and immunoglobulin class switching. Since B-cell abnormalities including hypergammaglobulinemia and abnormal antibody-specific immune responses are prominent and occur early during the course of pediatric human immunodeficiency virus (HIV) infection, we measured the baseline levels and the induced levels of expression of CD154 on CD3(+) CD8(−) (T helper cells) in HIV-infected children and uninfected children born to HIV-positive mothers. The percentage of CD154(+) T helper cells activated in vitro and the level of CD154 expressed per T helper cell (mean fluorescent channel [MFC]) were significantly lower in the HIV-infected children than in the uninfected control group (77% ± 3% versus 89% ± 1%, respectively [P < 0.002], and 261 ± 174 versus 415 ± 130 MFC, respectively [P < 0.03]). The levels of CD154 expressed on resting T helper cells in the HIV-infected group were not significantly different from the levels observed in the control group. In the HIV-infected children, the level of CD154 on activated T helper cells correlated with the level of immunodeficiency, as assessed by the CD4 T-cell levels (correlation coefficient [r] = 0.707, P = 0.003), but did not correlate with the viral load or with any of the serum immunoglobulin concentrations measured in this group of HIV-infected children. The baseline level of CD154 expressed on T helper cells did, however, correlate with the concentration of immunoglobulin A in serum. We conclude that HIV-infected children have impaired regulation of CD154 expression which may contribute to the immune dysregulation commonly observed.